1979
DOI: 10.1073/pnas.76.10.5056
|View full text |Cite
|
Sign up to set email alerts
|

Essential role for mevalonate synthesis in DNA replication

Abstract: The relationship between 3-hydroxy-3-methylglutaryl (HMG) CoA hibitor compactin, the normal S-phase burst of DNA synthesis was specifically and totally prevented. Finally, the compactin-induced inhibition of DNA synthesis could be completely reversed within minutes by the addition of mevalonate, the product of the HMG CoA reductase reaction. By contrast, addition of cholesterol-rich lipoproteins had no effect upon DNA synthesis in compactin-treated cells. These data demonstrate that HMG CoA reductase activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
0
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(130 citation statements)
references
References 26 publications
7
122
0
1
Order By: Relevance
“…We have shown, however, that mevalonate at concentrations as high as 1 mM has no effect on the proliferation of human umbilical vein endothelial cells or their ability to form tubules in Matrigel. 2 Furthermore, medium conditioned with mevalonate-pretreated MDA-MB-435 cells also had no effect on the proliferation of human umbilical vein endothelial cells in culture and, indeed, inhibited the formation of tubules by these cells in Matrigel. 2 These observations suggest that mevalonate does not promote the growth of tumors by enhancing their ability to neovascularize and may even inhibit this process.…”
Section: Fig 4 Mevalonate Increases Cdk-2 Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown, however, that mevalonate at concentrations as high as 1 mM has no effect on the proliferation of human umbilical vein endothelial cells or their ability to form tubules in Matrigel. 2 Furthermore, medium conditioned with mevalonate-pretreated MDA-MB-435 cells also had no effect on the proliferation of human umbilical vein endothelial cells in culture and, indeed, inhibited the formation of tubules by these cells in Matrigel. 2 These observations suggest that mevalonate does not promote the growth of tumors by enhancing their ability to neovascularize and may even inhibit this process.…”
Section: Fig 4 Mevalonate Increases Cdk-2 Activitymentioning
confidence: 99%
“…As might be expected, these effects are the converse of cell cycle events that follow mevalonate depletion in cultured cells treated with statins (2). It has been known for some time that a critical level of mevalonate or an as yet unidentified nonsterol metabolite of mevalonate is required for initiation of DNA synthesis (2). Inadequate intracellular levels of mevalonate prevent entry of cells into S phase, resulting in a characteristic G 1 phase growth arrest (2, 38).…”
Section: Fig 2 Mevalonate Promotes the Growth Of Mda-mb-435 Human Cmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that lovastatin disrupts early signaling events such as tyrosine phosphorylation levels of the PDGF receptor and its association with PI-3-kinase (McGuire et al, 1993). Moreover, lovastatin arrests cultured cells predominantly in the G 1 phase of the cell cycle and produces a characteristic rounded morphology (Quesney-Huneeus et al, 1979;Sinensky and Logel, 1985;Fenton et al, 1992). Lovastatin has also been found to inhibit tumor growth of cells expressing oncogenic H-Ras in nude mice, but at doses that blocked tumor growth, lovastatin was extremely toxic and some animals died (Sebti et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…DEHP is lipophilic and can suppress the activity of HMG CoA reductase (3-hydroxy-3-methylglutaryl CoA reductase, EC 1.1.1.34) which is the enzyme responsible for the regulation of de novo cholesterogenesis (23). This action could provide one mechanism by which DEHP might suppress cell growth since intermediates from the synthesis of cholesterol appear to be required for cell division (24,25). We are currently studying another group of membrane-bound enzymes which appear to be affected by DEHP.…”
Section: Resultsmentioning
confidence: 99%